Environmental changes and collective bargaining priorities: analysis, implications and outline for future research - Che Rose, Raduan; Samy, Naresh Kumar; Gani, Harris (The Journal of International Social Research, 2008)
There has been limited attempt to examine the issue of collective bargaining, the changes in the larger industrial relations environment and the impact of these changes on Malaysian trade union movement. Thus a study was conducted to enhance the understanding of the process of collective bargaining and the underlying environment within which it is conducted. The emphasis is to examine the nature, extent, and scope of changes in the sector/industry environment, management strategies, workplace practices, and work environment and how they shaped collective bargaining priorities among private sector employee unions in Malaysia. The findings of this research have several practical and theoretical implications.